2013
DOI: 10.1159/000351142
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patient-Reported Stroke Outcomes: A Validation of the Six Simple Variable Prognostic Model

Abstract: Background: Case-mix represents the range of disease severity and baseline characteristics that may be the cause of variation in outcomes between individuals and populations. Adjustment for case-mix is therefore important to allow meaningful comparison of healthcare outcomes. The best available case-mix adjustment model for stroke (the Six Simple Variable [SSV] model) was developed to adjust the hard endpoints of independent survival, survival and alive and living at home. There is increasing interest in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Regarding the meaning of a longer hospital stay and an increased time of rehabilitation, doubts about the effective impact of these variables remain (we found 1 % increased chance of better outcome for every day of rehabilitation). Previous literature reported discordant results about the impact of longer hospital stay and rehabilitation on functional outcomes after stroke, with some authors finding positive results [11,30,31], whereas others a negative impact [32].…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the meaning of a longer hospital stay and an increased time of rehabilitation, doubts about the effective impact of these variables remain (we found 1 % increased chance of better outcome for every day of rehabilitation). Previous literature reported discordant results about the impact of longer hospital stay and rehabilitation on functional outcomes after stroke, with some authors finding positive results [11,30,31], whereas others a negative impact [32].…”
Section: Discussionmentioning
confidence: 93%
“…SSV is a prognostic scale that includes pre-stroke living arrangements and independence, and post stroke orientation, arm movement, mobility and verbal response. 7 We assessed SSV as an ordinal scale, in aggregate and individual components, and as a quasi-continuous measure including age. 8 SSV is used as a case-mix adjuster in trials and has been shown to have excellent prognostic utility.…”
Section: Analysesmentioning
confidence: 99%
“…8 SSV is used as a case-mix adjuster in trials and has been shown to have excellent prognostic utility. 7 Age and NIHSS were combined to calculate SPAN score, another validated prognostic scale. 9 We described association for the complete group and subgroups of 90-day survivors and those admitted from home.…”
Section: Analysesmentioning
confidence: 99%
“…Adjustment for case-mix and the use of patient or family-reported outcomes in future studies may help improve prognostication, but, importantly, such models will always suffer from this inherent limitation. [33, 34] Models that predict functional recovery are also limited by the challenges in predicting an individual patient's ability to adapt (“response shift”) to a neurologic deficit that the patient has not yet experienced, as well as reframing or changing perceptions of quality of life that can occur over time. [35, 36]…”
Section: Introductionmentioning
confidence: 99%